Burnout of school principals in Poland: work demands, resources, and stressors - Kołodziejczyk, Joanna; Mazurkiewicz, Grzegorz; Kołodziejczyk, Jakub (Frontiers in Public Health, 2025)
BackgroundSchool principals face increasing professional challenges and psychological strain, amplified by extra-organizational stressors such as political and systemic changes, climate change, war, and economic instability. These factors can elevate job demands and increase the risk of professional burnout.MethodsThis study examined the relationship between burnout among 117 Polish public school principals and their subjective perception of extra-organizational stressors as well as the use of job resources. Burnout was measured using the Oldenburg Burnout Inventory, while support sources and perceived external pressures were assessed via a custom questionnaire. Multiple regression analyses were conducted to assess predictive relationships.ResultsBurnout was significantly associated with perceptions of changes in the educational system. Institutional support from the education system was linked to lower burnout levels, while support via social media was associated with higher burnout and disengagement. Other factors, such as concerns about the economy, climate change, and war, were not significantly associated with burnout.ConclusionFindings highlight the critical impact of systemic educational reform as a unique stressor contributing to burnout among school principals. Institutional support appears to buffer this effect, while reliance on informal networks such as social media may reflect deeper professional distress. These results suggest the need for structural support mechanisms tailored to school leadership roles.